Shear behaviour of permanent precast formwork beams - Mansor, Shariwati (2015)
An experimental research was conducted to evaluate the shear capacity of permanent precast formwork beams and compared to normal cast in-situ concrete beams. The traditional approach of normal construction uses conventional timber and plywood, which requires laborious and time consumption of installation. This paper studies the shear behaviour of permanent precast concrete beams using different glass fibre volume (ranging from 0% and up to 1%) in mortar mixes to act as permanent formwork. The mechanical properties tests involved in the mortar were compressive and flexural strength tests. The optimum content of glass fibre then was determined based on several trial mixes made beforehand. Two permanent precast formwork beams, one used 0.52% of glass fibre and the other one used wire mesh were tested under av/d = 1.5 and compared with normal control beam. All beam specimens were tested to obtain the ultimate shear load. The results showed that permanent precast formwork beam with wire mesh gave better performance in terms of ultimate load. Measured shear capacities of the tested beams were then compared with the theoretical values calculated according to BSEN1992:2004.